Targeting EGFR and Monitoring Tumorigenesis of Human Lung Cancer Cells In Vitro and In Vivo Using Nanodiamond-Conjugated Specific EGFR Antibody - Yu-Wei Lin; Hung-Cheng Su; Emmanuel Naveen Raj; Kuang-Kai Liu; Chien-Jen Chang; Tzu-Chia Hsu; Po-Yun Cheng; Rou-Hsin Wang; Yen-Her Lai; Chien-Hung Chen; Yen-Cheng Lin; Jui-I Chao (MDPI AG, 2022)
Nanoprobes provide advantages for real-time monitoring of tumor markers and tumorigenesis during cancer progression and development. Epidermal growth factor receptor (EGFR) is a key protein that plays crucial roles for tumorigenesis and cancer therapy of lung cancers. Here, we show a carbon-based nanoprobe, nanodiamond (ND), which can be applied for targeting EGFR and monitoring tumorigenesis of human lung cancer cells in vitro and in vivo. The optimal fluorescent intensities of ND particles were observed in the human lung cancer cells and nude mice under in vivo imaging system. The fluorescence signal of ND particles can be real-time detected in the xenografted human lung tumor formation of nude mice. Moreover, the ND-conjugated specific EGFR antibody cetuximab (Cet) can track the location and distribution of EGFR proteins of lung cancer cells in vitro and in vivo. ND-Cet treatment increased cellular uptake ability of nanocomposites in the EGFR-expressed cells but not in the EGFR-negative lung cancer cells. Interestingly, single ND-Cet complex can be directly observed on the protein G bead by immunoprecipitation and confocal microscopy. Besides, the EGFR proteins were transported to lysosomes for degradation. Together, this study demonstrates that ND-conjugated Cet can apply for targeting EGFR and monitoring tumorigenesis during lung cancer progression and therapy.